Capnocytophaga Canimorsus Infection in Cats: ABCD guidelines on prevention and management. Issue 7 (July 2013) - Lloret, Albert; Egberink, Herman; Addie, Diane; Belák, Sándor; Boucraut-Baralon, Corine; Frymus, Tadeusz; Pennisi, Maria Grazia; Gruffydd-Jones, Tim; Hartmann, Katrin; Hosie, Margaret J; Lutz, Hans; Marsilio, Fulvio; et al.
Overview: Capnocytophaga canimorsus and Capnocytophaga cynodegmi are part of the normal bacterial flora of the oral cavity of dogs and cats. C canimorsus is more pathogenic and causes more severe infections in humans. Infection: Disease is less frequently seen after a cat bite, scratch or close contact than after dog contacts. Serious disease has been reported in people, especially associated with immunocompromise and alcoholism. Disease in cats is not well documented; two cases of respiratory infection have been associated with the presence of these bacteria. Diagnosis: Diagnosis is based on culture in specific media, but these are slow growing bacteria; polymerase chain reaction and sequencing may aid in diagnosis and species identification. Treatment: Penicillin or beta-lactams are the treatment options of choice. Zoonotic potential: Based on incidence surveys, the zoonotic potential is low. The risk may be higher for immunocompromised persons, where dog and cat ownership must be discussed.